Detection of delayed focal MR changes in the lateral hippocampus in transient global amnesia - Sedlaczek, Oliver; Hirsch, J. G.; Grips, Eva; Peters, C. N. A.; Gass, Achim; Wöhrle, Johannes C.; Hennerici, Michael G. (Neurology, 2004)
BACKGROUND: There is still limited knowledge on the location and etiology of transient global amnesia (TGA). MR studies including diffusion-weighted imaging (DWI) have been unable to demonstrate consistently the location and underlying pathology of TGA. - OBJECTIVE: To investigate patients with TGA using serial DWI performed from the day of symptom onset through days 1 and 2. - METHODS: After reporting negative DWI results in a previous study, the authors used a modified study design to investigate patients with TGA using serial DWI performed from the day of symptom onset through days 1 and 2. - RESULTS: Of 31 consecutive patients studied, 26 developed a small, punctate DWI lesion in the lateral aspect of the hippocampal formation (pes and fimbria hippocampi) on either side (left, n = 15; right, n = 6) or bilaterally (n = 5). Lesions were rarely noted in the hyperacute phase (n = 2), but all became visible regularly at 48 hours. - CONCLUSIONS: The study confirms the involvement of hippocampal parenchyma in the pathophysiology of TGA. The delayed detectability of the lesions may explain the incongruence of previous MR DWI studies in TGA patients.
Gesehen am 19.05.2022